Fragmentos de um quadro ou o que as migalhas do cotidiano nos contam: prática votiva no mundo luso-brasileiro (séculos XVIII e XIX) - Weslley Fernandes Rodrigues (2018)
This study discusses votive practices in the Luso-Brazilian world in the 18th and 19th centuries from a comparative perspective, as based on existing Portuguese and Brazilian collections of ex-votos paintings. Considering its importance and endurance in Catholic worship, this practice is investigated in the present thesis in an attempt to understand the role it played in the relationship between Christendom religiosity in the aforementioned period and the Church's effort to normalize the behavior of faithful Catholics throughout history. To this end, an effective analysis entails understanding the process of renewal through which the Church passed from the sixteenth century onwards with the Council of Trent. Recurrently, the historiography of religion recognizes the importance of this moment for the Catholic organization the following centuries, both in Europe and in the process of evangelization ofother peoples. However, the importance of the Council of Trents resolutions is often understood a priori, without a proper observation of the impact these determinations had in the daily life of Christendom. This text therefore seeks to analyze the meaning of the Trent decrees in the development of votive practice. Two important votive practice-related aspects were thus chosen, namely: the sacred figure artistic representation and the potential intervention of the saints in the daily life of the faithful Catholics. The purpose of this thesis is therefore to analyzehow this religious expression, as materialized by the ex-votos paintings primitively showcased in chapels and churches, is associated with the doctrines and norms typical of Catholic worship. The thesis is structured as follows: the first part correlates the presence of saint figures in theLuso-Brazilian ex-votos paintings with the Churchs sacred representation resolutions, using long-term history for the understanding of such correlation; from the stories present in painted tablets, the second part resorts to microhistory to investigate the importance individuals attributed to the communion of saints doctrine, which was used as a key element to comprehend a daily life permeated by nefariousness